Anatomical Patterns of the Pancreatic Ductal System – A Cadaveric and Magnetic Resonance Cholangiopancreatography Study - Prasad, Mythraeyee; Rout, Sipra; Putta, Tharani; Kurien, Reuben Thomas; Chowdhury, Sudipta Dhar; Eapen, Anu; Hepsy, Y. S.; Rabi, Suganthy (Journal of Morphological Sciences, 2019)
Introduction Morphological variants of the pancreatobiliary system can predispose to chronic pancreatitis. The goal of the present study is to assess the prevalence of pancreatic duct patterns in the Indian population, both by cadaveric dissection and by magnetic resonance cholangiopancreatography (MRCP).Materials and Methods A total of 15 adult pancreas specimens of unknown age and gender, and 5 fetal pancreas specimens of different gestational ages with the intact second part of duodenum, were dissected by the piecemeal method. For clinical relevance, MRCP images of 103 clinically-diagnosed chronic pancreatitis patients irrespective of their etiology were obtained retrospectively from the existing database and studied. The anatomical patterns were classified as five different types based on the course of the main pancreatic duct and the accessory pancreatic duct and their openings into the duodenal wall, including variants like pancreas divisum and ansa pancreatica.Results In the cadaveric study, the main pancreatic duct was single with a straight course in 46.67% of the adult specimens, and in the MRCP study, the main pancreatic duct showed a descending course in 77.66% of the cases. The most common pattern was type III in both the cadaveric (80%) and radiological (55.33%) studies, and the accessory duct was absent on the MRCP in all type-III cases, while it ended blindly in the cadaveric specimens. Ansa pancreatica (type V) was observed in 1 adult specimen (6.7%), but not in the radiological study. Pancreas divisum (type IV) was observed in the 8 cases (7.76%) cases in the radiological study.Conclusion Knowledge of the anatomical variants of the pancreatic ductal system may be helpful for the radiologists during diagnostic and therapeutic interventional procedures.
Keywords: pancreas; pancreatic ductal pattern; ansa pancreatica; pancreas divisum; magnetic resonance cholangiopancreatography